Functional Roles of Poly(ADP-Ribose) in Stress Granule Formation and Dynamics - Jin, Xuejiao; Cao, Xiuling; Liu, Shenkui; Liu, Beidong (Frontiers in Cell and Developmental Biology, 2021)
Stress granules (SGs) are highly dynamic cytoplasmic foci formed in response to stress. The formation of SGs is reported to be regulated by diverse post-translational protein modifications (PTMs). Among them, ADP-ribosylation is of emerging interest due to its recently identified roles in SG organization. In this review, we summarized the latest advances on the roles of poly(ADP-ribose) (PAR) in the regulation of SG formation and dynamics, including its function in modulating nucleocytoplasmic trafficking and SG recruitment of SG components, as well as its effects on protein phase separation behavior. Moreover, the functional role of PAR chain diversity on dynamic of SG composition is also introduced. Potential future developments on investigating global ADP-ribosylation networks, individual roles of different PARPs, and interactions between ADP-ribosylation and other PTMs in SGs are also discussed.